(untitled) (CIPEEX, 2025)
During the undergraduate medical course, students must experience the practice of FCM, with the aim of developing the following behaviors: coexistence and collaboration with professionals from other professions, knowledge of the social determinants of health, humanized care for patients and their families, and the development of health promotion, protection, and education projects. Health promotion is an important strategy to increase the quality of life and the population’s access to health services. It is a set of actions and policies that aim to empower individuals and communities to improve and control their own health, going beyond disease prevention, and instead adopting a proactive approach based on education and the creation of aggregating and healthy actions. METHODOLOGY: This is a study classified as descriptive, of the experience report type, based on the experiences, learning, and perceptions of 2nd-year medical students in relation to the CMEI Rainha da Paz, located in Anápolis, a city in the state of Goiás, and the concept and application of the Arco de Maguerez. It describes how each stage of the Arc was carried out and the importance of understanding and applying the Arc of Maguerez as a mechanism for bringing the Vívian Parque Basic Health Unit and the associated community closer together. RESULTS: The Rainha da Paz Early Childhood Education Center (CEI) is located in the Vivian Parque neighborhood, an urban area of ​​the city of Anápolis. The institution consists of several classrooms, a courtyard for socializing, a boardroom, a secretary’s office, a storeroom, bathrooms and bathrooms with showers, a cafeteria, and a covered and uncovered recreation area. When formulating strategies for implementing the project, the academics provided a playful environment that directed attention and interest, providing a space to incorporate new knowledge, as well as to recover and formalize previously well-established practices. The different forms of participation, such as encouraging the game of jumping hopscotch to remove a surprise item from the “hygiene box” (Figure 1), were essential in establishing a bond and dialogue, facilitating an effective discussion of the health topic addressed. The lecture with parents consisted of addressing the myths and truths most frequently reported by CMEI employees, which were sources of daily problems in the school environment. The presentation was led by the physician in charge, using an interactive dynamic with “myth” or “truth” signs, handed out to the participants to encourage active participation by all. In addition, at the end, a space was opened for questions, allowing doubts to be clarified. CONCLUSION: The reported study provides a comprehensive overview of the practical application of the Maguerez Arc in the context of Family and Community Medicine (FCM). This study reinforces the importance of continuous practice and the application of theoretical models in real public health contexts, offering valuable insights for the training of health professionals and for the development of effective community interventions. Future research can explore the replication of these practices in different contexts and evaluate the long-term impact of the educational interventions carried out.